IMPLEMENTATION OF THE USE OF THE TSAWAB (REWARD) AND IQAB (PUNISHMENT) METHODS IN IMPROVING THE ABILITY TO LEARN TAHFIZHUL QUR'AN - Aziz, Mursal; Napitupulu, Dedi Sahputra; Sagala, Nurdalila Armita (Jurnal Ilmiah Didaktika, 2025)
At an early age, children's memorization abilities develop rapidly, making this period a crucial time to instill the habit and ability to memorize the Qur'an. At TK Islam Ridho Walidaina, the Qur'an memorization program is one of the main focuses in learning. However, achieving memorization targets is often a challenge due to children's fluctuating motivation and difficulty in maintaining focus. Therefore, this study aims to determine the effectiveness of using the Tsawab (reward) and Iqab (punishment) methods in improving the ability to memorize the Qur'an in children at Ridho Walidaina Islamic Kindergarten. In this study, the researcher used the type of classroom action research (CAR), by conducting case studies to research problems in the classroom during learning with the aim of improving or increasing the quality of learning. The results of the study showed that the Tsawab (reward) and Iqab (punishment) methods were effective in improving students' ability to memorize the Qur'an. In Cycle I, only 66.6% of students successfully completed the memorization, indicating the need for improvement. After the application of more intensive methods in Cycle II, the percentage of success increased significantly to 85.7%. This shows that giving rewards and punishments helps improve children's motivation and discipline in memorizing the Qur'an.